Abnormal white matter microstructure among early adulthood smokers: a tract-based spatial statistics study. (2nd December 2017) - Wang, Shuangkun; Zuo, Long; Jiang, Tao; Peng, Peng; Chu, Shuilian; Xiao, Dan
Abstract: Objectives: Cigarette smoking is an important risk factor of central nervous system diseases. However, the white matter (WM) integrity of early adulthood chronic smokers has not been attached enough importance to as it deserves, and the relationship between the chronic smoking effect and the WM is still unclear. The purpose of this study was to investigate whole – brain WM microstructure of early adulthood smokers and explore the structural correlates of behaviorally relevant features of the disorder. Methods: We compared multiple DTI-derived indices, including fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD), between early adulthood smokers ( n  = 19) and age-, education- and gender-matched controls ( n  = 23) using a whole-brain tract-based spatial statistics approach. We also explored the correlations of the mean DTI index values with pack-years and Fagerström Test for Nicotine Dependence. Results: The smokers showed increased FA in left superior longitudinal fasciculus (SLF), left anterior corona radiate, left superior corona radiate, left posterior corona radiate, left external capsule (EC), left inferior fronto-occipital fasciculus and sagittal stratum (SS), and decreased RD in left SLF. There were significant negative correlations among the average FA in the left external capsule and pack-years in smokers. In addition, significant positive correlation was found between RD values in the left SLF and pack-years. Discussion: These findings indicate that smokers show microstructural changes in several white-matter regions. The correlation between the cumulative effect and microstructural WM alternations suggests that WM properties may become the new biomarkers in practice.